Controllable Polarization Rotator with Broadband High Transmission Using All‐Dielectric Metasurfaces. Issue 9 (25th June 2019) - Li, Zhiwei; Cai, Xiaodong; Huang, Lirong; Xu, Hao; Wei, Yunbing; Dai, Ning
Abstract: In recent years, how to fully manipulate the polarization state of linearly polarized (LP) light has become an emerging research hotspot in the region of photonics. Here, a novel alternative approach based on all‐dielectric metasurfaces to realize and control the polarization state of light with broadband and high transmission is theoretically and numerically investigated. In contrast with the polarization rotation mechanism of non‐chiral metasurfaces, the proposed configuration can be illustrated by the Jones matrix in a theoretical analysis. The proposed design is based on multi‐conversion of the incident linearly polarized light in a double‐layer quarter‐wave plate structure. Through an elaborate design of the structural units, a one‐layer quarter‐wave plate structure can convert a linearly polarized light to a circularly polarized state. An arbitrary polarization rotation with high efficiency (>88%) and broadband (approximately equal to the bandwidth of quarter‐wave plate) can be achieved through the collective effect of the two quarter‐wave plates. The proposed approach based on all‐dielectric metasurfaces exhibits the capacity of arbitrarily manipulating the polarization states, which can facilitate future applications in photonics. Abstract : The proposed design is obtained from multi‐conversion in a double‐layer quarter‐wave plate structure for the incident linearly polarized light, which is illustrated by the Jones matrix in a theoretical analysis. Through the collective effect of two quarter‐wave plates, an arbitrary polarization rotation with high efficiency and broad bandwidth can be achieved.